Epidemiology of Botulism in Sheep and Goats in Northern Localities of North Kordofan State, Sudan - Ibrahim, A.A.; Shigidi, M.T.A. (Journal of Veterinary Medicine and Animal Production, 2021)
Suspected cases of botulism were first noticed among sheep and goats flocks in Northern Localities of North Kordofan State, which was struck by waves of drought. Poor pasture and nutritional deficiency, forced the animal to develop pica and chew dead carcasses which were the major source of the toxin. The purpose of this study is to determine the factors associated with the occurrence of the disease and the source if intoxication. Methodology involved the description of the area of the disease outbreak, and the disease patterns. Attempts were made to reproduce the disease by drenching susceptible animals with extracts from carcasses and to trace the possible origin the disease agent. Observations revealed that the area of the outbreak was covered with only few plant species and animals developed pica. The disease occurred in sheep and goats only, and among these, pregnant, lactating, and yearlings were most affected. The temporal pattern of the disease showed a rapid increase in the number of new cases over a short period of time, while the spatial pattern showed wide a geographical distribution of the disease. Drenching susceptible animals with suspected carcass material, resulted in the production of the disease, with symptoms similar to those observed in the natural outbreak. As botulism was endemic in Libya since 1980s, It is possible that the organism and its spores were carried over from Libya to Sudan by carrion-eating birds and movement of animals, man, and vehicles.